1990
DOI: 10.1111/j.1151-2916.1990.tb05226.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐Pressure Self‐Combustion Sintering of Alumina‐Titanium Carbide Ceramic Composite

Abstract: AI2O3-TiC ceramic composites were fabricated by highpressure self-combustion sintering (HPCS). The samples had a unique microstructure which was quite different from that of commercial A1203-TiC materials made by conventional processing. A possible mechanism for combustion reaction is suggested on the basis of the microstructure of the samples and the thermodynamical data. The HPCS sample had a higher KIc value than commercial A1203-TiC materials.[

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…3 indicate that the liquid alumina phase exists during the combustion synthesis. Adachi et al [5] and Bowen and Derby [6] reported evidence of melting of alumina in the combustion synthesis of Al 2 O 3 ±TiC composites.…”
Section: Resultsmentioning
confidence: 97%
“…3 indicate that the liquid alumina phase exists during the combustion synthesis. Adachi et al [5] and Bowen and Derby [6] reported evidence of melting of alumina in the combustion synthesis of Al 2 O 3 ±TiC composites.…”
Section: Resultsmentioning
confidence: 97%
“…Since the starting TiO 2 phase has the anatase modification, the presence of rutile in the quenched-reaction zone is an indication of a solid-solid transformation of titania, a process that takes place at 918 K. The presence of titanium in this zone is consistent with the two-step mechanism mentioned above and is in agreement with reports in the literature. 3,12,13 The differential thermal analysis (DTA) study by Sundaram et al 16 on the system 4Al⅐3TiO 2 has shown that the reaction between Al and TiO 2 at 1165 K leads to the formation of Ti 3 Al according to…”
Section: Resultsmentioning
confidence: 99%
“…(1) result in a value of 2329 K when the initial temperature is 298 K and a value of 2394 K when the latter temperature is 400 K. Although the measured maximum temperature is lower than the melting temperature of alumina, there is microstructural evidence in this work (to be discussed later) and in previously published accounts that melting of this phase does take place. Adachi et al 12 and Bowen et al 13 reported evidence of melting of alumina in the combustion synthesis of Al 2 O 3 -TiC composites. During the short duration of the main combustion reaction, liquid aluminum reacts with rutile particles and liquid Ti, Ti 3 Al, and alumina surround the fine rutile particles or rutile particles dissolved into the liquid mixture ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be explained by noting that the combustion wave velocity is a strong function of the combustion temperature, which is higher in the case of anatase, as shown in Fig. 6 The XRD pattern indicates that the product is composed of only two major phases, TiC and A12O3. The bond strength between Ti and O in anatase TiO2 is calculated to be approximately 6 kJ/mole lower than that in rutile TiO2, and as a result, it facilitates the aluminothermic reduction of TiO2 in the 3TiO2-4Al-3C system and enhances the reactivity of the sample.…”
Section: Methodsmentioning
confidence: 95%